Markernas kronologi och ideologi i norra Sverige Natur och språkligt platsskapande med fokus på nybyggarkolonisationen under 1700- och 1800-talet - Andersson, Daniel (Kriterium, 2023)
Narratives about northern Sweden are often narratives about nature. This has been true throughout history and is still true today. Different ways of understanding nature have become intertwined with the place and the people who live there. The nature in northern Sweden can be magnificent and impressive, but it can also be desolate, threatening and dangerous. A dominant image of nature in northern Sweden - then as now - is the image of resources, assets. The overall aim of the study is to shed light on the role of nature in linguistic place-making in northern Sweden with a particular focus on the settler colonization during the 18th and 19th centuries. Through a selection of text sources, nature's central place in the story of the colonization, of the place, its history, change and future is highlighted. The texts that are analyzed are the two journals in which Petrus Læstadius described his work as a missionary in Lapland, as well as Olov Petter Pettersson's detailed description of the settler colonization in the work Gamla byar i Vilhelmina. The settler colonization took place in areas with Sami presence and history and this study connects to the research field of Settler Colonial Studies in a critical discussion of the linguistic place-making in the texts. One of the aims of the study is to also shed light on the connections that exist between the settler colonization depicted in the texts, and the linguistic place-making with nature at the center that is ongoing in northern Sweden today.